THE ROLE OF TRAINING AND DEVELOPMENT IN IMPROVING HUMAN RESOURCE PERFORMANCE IN CULINARY MSME INDUSTRY - Masri, La Ode Mohammad; Mokodompit, Eliyanti Agus (Penelitian dan Pengembangan Ilmu, 2024)
Training and development of Human Resources (HR) has a very important role in improving performance and competitiveness in various industrial sectors, including culinary MSMEs. Although many studies highlight the importance of training in large companies, there are still few that examine the application of training in culinary MSMEs, especially in relation to the limited resources they have. The gap in this research lies in the lack of studies that measure the direct impact of training on employee performance in the culinary MSME sector, especially in the development of soft skills such as customer service. This study uses a descriptive qualitative approach with in-depth interviews with MSME owners, HR managers, employees, coaches, and HR management experts to identify the impact of training on HR performance in culinary MSMEs. The findings of this study contribute to understanding the importance of training tailored to the specific needs of employees and show that technology-based training can be an efficient solution for MSMEs with limited time and resources. This research can provide practical solutions for culinary MSMEs in designing relevant and efficient training programs to improve the performance and competitiveness of culinary businesses.